The Implications of Filial Piety in Study Engagement and Study Satisfaction: A Polish-Vietnamese Comparison - Różycka-Tran, Joanna; Jurek, Paweł; Truong, Thi Khanh Ha; Olech, Michał (Frontiers in Psychology, 2021)
Even in psychological literature, which describes many determining variables related to the school domain, few studies have investigated the universal (i.e., etic) mechanism underlying parent–child relations, which is a prototype matrix for future student–teacher relations. The role of the imprinted schema of children’s obligations toward parents seems to be crucial for school functioning in classroom society. The Dual Filial Piety Model (DFPM; Yeh, 2003) is comprised of two higher-order factors that correspond to the two focal filial piety attributes: reciprocal (need of interpersonal relatedness) and authoritarian (need of social belonging and national identity), which have been shown to have distinct implications on social adaptation and individuals’ psychological functioning. In this study, we investigate the relationship between filial piety and student attitudes (study engagement and satisfaction) in a more individualistic and egalitarian culture (Poland, N = 310) and in a more collectivistic and hierarchical society (Vietnam, N = 297). The measurement invariances of three scales, i.e., the Vietnamese adaptation of DFP Scale, the Utrecht Work Engagement Scale (UWES–S9), and the Study Satisfaction Scale, were improved in the MLM analyses. Our results show that in more individualistic cultures, the RFP (reciprocal mode) is a stronger predictor of study engagement and study satisfaction; however, the AFP (authoritarian mode) is a better factor to predict study engagement in more collectivistic cultures. What is more, only RFP positively correlates with study satisfaction in individualistic culture. Our findings revealed that in different cultures, different aspects of filial piety should be emphasized by parents in the context of the future academic achievements of their children. The conclusion is that the prevention and intervention strategies or techniques intended for children with school problems should be culturally appropriate and addressed to the parents of kindergarten and later to very early-stage education teachers. The results of studies based on the DFPM may stimulate practical applications and policy development within the domain of success and failure in the academic environment.